Peningkatan efisiensi produksi sangkar burung Desa Tanjung - Salsabila, Fina; Hanisah, Isnaeni Hasna; Indrasto, Haryo Bimo Budi; Abidin, Ali Zainal (Penamas: Journal of Community Service, 2025)
This community service activity was carried out from February to April 2025 in Tanjung Village, Juwiring District, Klaten Regency, with a focus on empowering UMKM birdcage producers in terms of financial management and branding strategies. The objects or partners in this activity were 20 birdcage producers who were members of a local business group. The implementation of the activity was carried out through training methods and direct mentoring. Training materials include simple financial recording, cash flow management, separating personal and business finances, and utilizing digital applications for recording daily transactions. Additionally, mentoring was provided in formulating branding strategies to enhance product appeal and market recognition. Based on the results of the activity, there was an increase in understanding among business actors regarding the importance of systematic financial recording, as well as a growing awareness of the significance of brand identity. This activity is expected to encourage the sustainability and growth of birdcage producers’ businesses.